Chromospherically active stars in the RAVE survey: II. Young dwarfs in the solar neighborhood - Žerjal, Maruška; Grebel, Eva K. (Arxiv, 2016)
A large sample of over 38,000 chromospherically active candidate solar-like stars and cooler dwarfs from the RAVE survey is addressed in this paper. An improved activity identification with respect to the previous study was introduced to build a catalog of field stars in the Solar neighborhood with an excess emission flux in the calcium infrared triplet wavelength region. The central result of this work is the calibration of the age--activity relation for the main sequence dwarfs in a range from a few $10 \; Myr$ up to a few Gyr. It enabled an order of magnitude age estimation of the entire active sample. Almost 15,000 stars are shown to be younger than $1\;Gyr$ and $\sim$2000 younger than $100\;Myr$. The young age of the most active stars is confirmed by their position off the main sequence in the $J-K$ versus $N_{UV}-V$ diagram showing strong ultraviolet excess, mid-infrared excess in the $J-K$ versus $W_1-W_2$ diagram and very cool temperatures ($J-K>0.7$). They overlap with the reference pre-main sequence RAVE stars often displaying X-ray emission. The activity level increasing with the color reveals their different nature from the solar-like stars and probably represents an underlying dynamo generating magnetic fields in cool stars. 50% of the RAVE objects from DR5 are found in the TGAS catalog and supplemented with accurate parallaxes and proper motions by Gaia. This makes the database of a large number of young stars in a combination with RAVE's radial velocities directly useful as a tracer of the very recent large-scale star formation history in the Solar neighborhood. The data are available online in the Vizier database.